2005
DOI: 10.1097/01.mlg.0000161347.07881.6d
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Endoscopy Versus Modified Mallampati Score in Sleep Apnea and Snoring

Abstract: No positive correlation exists between a large tongue and obstruction at tongue base level. In both groups, retropalatal obstruction occurred more often than retrolingual obstruction. Sleep endoscopy provides qualitative insight into important changes during sleep in patients with SUS and OSAS. In addition, anatomic aberrations are clearly visualized in a dynamic setting. Classification of the size of the tongue, as assessed by the MMS, may be of great importance as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 16 publications
5
43
1
3
Order By: Relevance
“…This study correlates with the study conducted by Herder et al 13 He reported that, of 127 patients, 63% had single level obstruction while only 37% had multilevel disease. But study conducted by Riley et al shows 93.3% (223 patients) were identified as having multilevel obstruction.…”
Section: Discussionsupporting
confidence: 91%
“…This study correlates with the study conducted by Herder et al 13 He reported that, of 127 patients, 63% had single level obstruction while only 37% had multilevel disease. But study conducted by Riley et al shows 93.3% (223 patients) were identified as having multilevel obstruction.…”
Section: Discussionsupporting
confidence: 91%
“…The VOTE classification differs slightly from what we have developed independently for use in our practice [8,10,15,16] as it reflects the most fundamental aspects of the DISE evaluation. It does not prevent the addition of centerspecific assessments, but using a core classification and reporting the findings will advance our understanding of DISE, which has been limited to some extent by the wide diversity of systems in use around the world.…”
Section: Degree Of Airway Narrowingmentioning
confidence: 99%
“…Subjects with an AHI below 30/h, or, to be more accurate, patients with a supine AHI below 30/h and with good health (ASA I or II), can undergo midazolam-induced sleep endoscopy in the clinic [23,31]. Patients with a higher ASA score and/or more severe OSA should have DISE performed in the operating room.…”
Section: Dise: Sedation Methods Contraindications and Complicationsmentioning
confidence: 99%